Веселый солдат: [Повесть, рассказы] / Виктор Астафьев - Астафьев Виктор Петрович (Серия "Мастер")
Экземпляры: NLR () / Инвентарный номер: / Цена: / Сис.шифр: 99-5/5070 / Авт.знак: А 91 / ББК: Ш6(2=Р)75-44